[Maritime Union of Australia : ephemera material collected by the National Library of Australia]
The ephemera collection contains documents of everyday life generally covering publications of fewer than five pages. These may include: advertising material, area guides, booklets, brochures, samples of merchandise postcards, posters, programs, stickers and tickets.
Includes some material relating to the Seamen's Union.
Keywords: Maritime Union of Australia -- Miscellanea; Labor unions -- Australia -- Miscellanea; Stevedores -- Australia -- Miscellanea; Printed ephemera -- Australia; Australian